Integrated domain model for operative offshore installation planning - Daniel Rippel; Nicolas Jathe; Michael Lütjen; Helena Szczerbicka; Michael Freitag (Digital Transformation in Maritime and City Logistics: Smart Solutions for Logistics. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 28, 2019)
Purpose: This article aims to identify common structural elements in the descriptions of both approaches, enabling the application of model transformations. Methodology: Several models of both types will be compared, combining relevant concepts, i.e., entities, attributes and relationships into a generalized model. In a second step, elements crucial to either type of model are identified. For the remaining elements, interdependencies and redundancies will be identified to enable a model reduction. Findings: While the structure and notation of both approaches are different, both describe the same fundamental concepts and relationships. The article provides a data model of these common concepts for the operational planning of offshore activities, including weather restrictions and forecasts. Originality: In current literature, there exist no approaches to combine mathematical optimization with event-discrete simulations in the context of offshore wind farm installations. To harness the advantages of both approaches in an integrated methodology, a model of common concepts is required, which does not exist at this time.
urn:nbn:de:gbv:830-882.054571; 10419/209197; https://econpapers.repec.org/RePEc:zbw:hiclpr:28
Keywords: 650; Offshore wind energy; Operative installation planning; Domain model; Mathematical and simulation-based models